3x+(6+6y)=65

Simple and best practice solution for 3x+(6+6y)=65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+(6+6y)=65 equation:


Simplifying
3x + (6 + 6y) = 65

Remove parenthesis around (6 + 6y)
3x + 6 + 6y = 65

Reorder the terms:
6 + 3x + 6y = 65

Solving
6 + 3x + 6y = 65

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + 3x + -6 + 6y = 65 + -6

Reorder the terms:
6 + -6 + 3x + 6y = 65 + -6

Combine like terms: 6 + -6 = 0
0 + 3x + 6y = 65 + -6
3x + 6y = 65 + -6

Combine like terms: 65 + -6 = 59
3x + 6y = 59

Add '-6y' to each side of the equation.
3x + 6y + -6y = 59 + -6y

Combine like terms: 6y + -6y = 0
3x + 0 = 59 + -6y
3x = 59 + -6y

Divide each side by '3'.
x = 19.66666667 + -2y

Simplifying
x = 19.66666667 + -2y

See similar equations:

| 756.74=2*3.14*r^2+2*3.14*r*19.1 | | 2x+5-5x=-3x+2 | | 6b-8b=-3 | | 3(2x-8)-4=3(x-2)-7 | | 152=73.502+3.876 | | 41+x=2-2x | | 5x-92=97-2x | | x+x+1.81=68.11 | | Z+15=13 | | 5x-64=3x | | n*4-5=3 | | 3x=36-15x | | x+2(y-5)=2y+2 | | -4(3x+4)-2x+2=-2 | | 4(a+3)=18-2(3-2)a | | 3w+2=2-10 | | 7x-6=3x-54 | | 5(n+1)+2=3(n+1)+n | | 2x-20=10-3x | | 9x+4-7x=9x+4 | | 7(8x-1)=-7+6x | | 1133.9168=2*3.14*r^2+2*3.14*r*23.5 | | 9x+7y=35 | | -3(2x+9)=-4x | | 21x+6=17x-29 | | -3(5-2x)=4x+1 | | 4(x-6)=2(2x-12) | | 2x+3(7x-5)=192 | | x+23=35 | | 1b-73=-1b-3 | | 1+n=2n+9 | | 15b+2=-28 |

Equations solver categories